2016
DOI: 10.2174/187220830902160308195034
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemistry, Antinociceptive and Anti-inflammatory Actvities of Methanolic Leaves Extract of Lannea schimperi (Hoschst. Ex Rich) ENG.

Abstract: The patent data revealed the antinociceptive and anti-inflammatory potentials of the methanolic leaves extract of Lannea schimperi which could be beneficial in alleviating painful inflammatory conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Pharmacological studies on L. schimperi bark, leaf, root, and stem extracts exhibited potent in vitro and in vivo pharmacological activities including anesthetic [79], antibacterial [79,86], antifungal [86,87], anticoccidial [88], anti-inflammatory [82], antinoceceptive [82], antioxidant [83], anti-trypanosomal [89], antiulcerogenic [79], cytotoxicity [77,79,81,90], and toxicity [8,79] activities.…”
Section: Pharmacological Properties Of L Schimperimentioning
confidence: 99%
See 3 more Smart Citations
“…Pharmacological studies on L. schimperi bark, leaf, root, and stem extracts exhibited potent in vitro and in vivo pharmacological activities including anesthetic [79], antibacterial [79,86], antifungal [86,87], anticoccidial [88], anti-inflammatory [82], antinoceceptive [82], antioxidant [83], anti-trypanosomal [89], antiulcerogenic [79], cytotoxicity [77,79,81,90], and toxicity [8,79] activities.…”
Section: Pharmacological Properties Of L Schimperimentioning
confidence: 99%
“…Egbe et al [82] evaluated the anti-inflammatory activities of the methanolic leaf extracts of L. schimperi at doses of 12 mg/kg and 24 mg/kg using the egg albumin-induced acute inflammation model in rat with aspirin at dose of 80 mg/kg used as a positive control while the drug vehicle was used as a negative control. The extracts showed activities at both doses, and there were no significant differences between the extract treated rats with those rats treated with the standard drug, aspirin [82]. The exhibited anti-inflammatory activities of the methanolic leaf extracts of L. schimperi could be beneficial in alleviating painful inflammatory conditions.…”
Section: Anti-inflammatory Activitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…against various diseases. It has been shown that twigs induce apoptosis of human liver cancer cells [14] and leaves have antinociceptive [15], antioxidant [16], and antidiarrheal [17] activities. Barks were found to have anti-inflammatory [18], hypotensive [19], antihyperglycaemic [9], antimicrobial, antifungal [7], analgesic, and antioxidant effects [20], and the bark showed zoosporicidal activity [21].…”
Section: Introductionmentioning
confidence: 99%